PENERAPAN BAHAN AJAR TERINTEGRASI NILAI KARAKTER DALAM MODEL PEMBELAJARAN ADVANCE ORGANIZER PADA SISWA KELAS X SMA NEGERI 2 PADANG - Aldila Rahayu (Universitas Negeri Padang, 2014)
The teachers have to be able to develop their own learning instrumental, one is instructional material. Based on the demand of character education, the instructional material is needed to help the teachers to cultivate the character value to students. This research aims to know the effects of Implicating Intregated Material of Character Value in the Teaching Model Advance Organizer to the First Year Students of SMA Negeri 2 Padang. The type of the research is quasi-experimental. Population of the research is all students grade X of SMA Negeri 2 Padang year 2013/2014. Sample is taken by using clauster random sampling technique. The technique of data collection for cognitive domain is written test, while for affective and psychomotor domain is by doing obeservation. The technique of data analysis is by using t formula for cognitive and psychomotor domain, mean while for affective domain is descriptive data with graphics. Research findings acquire: 1) for cognitive domain tcount = 2,17 while ttable = 1,67 (in the area of refusal H0 until Hi accepted). 2) for psychomotor domain tcount = 6,42 while ttable = 1,67 (in the area of refusal H0 until Hi accepted). For affective domain, the character value is 80 in average. The conclusion is based on the hypothesis that ”there are meaningful effects of Implicating Intregated Material of Character Value in the Teaching Model Advance Organizer to the learning results of the First Year Students of SMA Negeri 2 Padang” are accepted in the real level of 0,05